PENINGKATAN PRESTASI BELAJAR IPS KOMPETENSI MEMAHAMI HUBUNGAN MANUSIA DAN BUMI MELALUI PENERAPAN METODE KOOPERATIF JIGSAW - Hartadi, Hartadi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
This study aims to improve learning achievement Social Sciences Competence understand human relationsand the earth through the application of jigsaw cooperative method. The subjects were students of class IX DSMP 5 Kudus, in the second semester of the school year 2013/2014, amounting to 34 students consisting of18 male students and 16 female students. The data collection techniques using tests, observations and fieldnotes. The results showed an increase both in teamwork and learning outcomes, observations discussiongroup activity on average in the first cycle of (69.21%), while in the second cycle increased to (77.26%).While the results of the evaluation showed that there was increase in the complete study of 24 students(70.59%) in the pre-action to 26 students (76.47%) in the first cycle and to 30 students (88.24%) in thesecond cycle.